EVALUASI PEMANFAATAN PUSTAKA GITA DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN BADUNG - Tani, Alexia Sipian Tani; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
The Office of Archives and Library of Badung Regency has launched the I-Badung digital library application which later changed its name to Pustaka Gita. The innovation of Pustaka Gita or this digital library is to provide services to the general public, blind people and elementary school students without being limited by space and time. This study aims to determine the evalvbuation of the use of the Gita Library application by explaining that this application is accepted and used properly or otherwise by users. This study uses a descriptive type of research with a quantitative approach using the Technology Acceptance Model (TAM) evaluation model. Data collection techniques in this study used observation, literature study and questionnaires with 2 independent variables and 3 dependent variables. The technique of determining the informants used purposive sampling (aimed at) with a total of 99 verified user respondents and had used the Gita Library application. The results of the study show that the Gita Library application has been beneficial for the people who use it but its utilization is still relatively low. Keywords : Evaluasi Pemanfaatan, Perpustakaan Digital, Pustaka Gita